Comparison of the neonatal outcomes of progestin-primed ovarian stimulation and flexible GnRH antagonist protocols: a propensity score–matched cohort study - Du, Mingze; Zhang, Junwei; Ren, Bingnan; Guan, Yichun (Frontiers in Endocrinology, 2023)
Objective: To compare the neonatal outcomes of progestin-primed ovarian stimulation (PPOS) and flexible gonadotropin-releasing hormone (GnRH) antagonist protocols. Methods: This was a retrospective propensity score–matched (PSM) cohort study. Women who underwent their first frozen embryo transfer (FET) cycle with freezing of all embryos followed by PPOS or GnRH antagonist protocols between January 2016 and January 2022 were included. Patients using PPOS were matched with the patients using GnRH antagonist at a 1:1 ratio. The main focus of this study was the neonatal outcomes of singleton live births, including preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA), macrosomia and large for gestational age (LGA). Results: After 1:1 PSM, a total of 457 PPOS and 457 GnRH antagonist protocols were included for analysis. The average starting dose of gonadotropin (275.1±68.1 vs. 249.3±71.3, P<0.01) and total dose of gonadotropin (2799.6±579.9 vs. 2634.4±729.1, P<0.01) were significantly higher in the PPOS protocol than in the GnRH antagonist protocol. The other baseline and cycle characteristics were comparable between the two protocols. The rates of PTB (P=0.14), LBW (P=0.11), SGA (P=0.31), macrosomia (P=0.11) and LGA (P=0.49) did not differ significantly between the two groups. A total of 4 patients in the PPOS group and 3patient in the GnRH antagonist group qualified as having congenital malformations. Conclusion: PPOS resulted in singleton neonatal outcomes similar to those of a GnRH antagonist protocol. The application of the PPOS protocol is a safe option for infertility patients.